1983
DOI: 10.1136/bmj.286.6377.1542
|View full text |Cite
|
Sign up to set email alerts
|

Method of sampling chorionic villi in first trimester of pregnancy under guidance of real time ultrasound.

Abstract: Samples of chorionic villi were obtained in the first trimester by aspiration using a cannula passed transcervically under the guidance of real time ultrasound. In initial studies in 47 anaesthetised patients immediately before therapeutic abortion a method was developed giving a success rate of 89%. In 10 patients successful sampling was performed as an outpatient procedure without anaesthesia. In all, seven diagnostic procedures were undertaken and four of the five unaffected pregnancies continued. The techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(45 citation statements)
references
References 5 publications
0
41
0
4
Order By: Relevance
“…We have also demonstrated that the ESD phenotypes can be easily demonstrated in fetal blood samples and in chorionic villus samples, thus permitting antenatal diagnosis during the first trimester (Ward et al, 1983;Rodeck et al, 1983). Although this enzyme polymorphism will be invaluable for the families reported here, because of the low frequency of the 2-allele in the UK will restrict widespread use.…”
Section: Resultsmentioning
confidence: 99%
“…We have also demonstrated that the ESD phenotypes can be easily demonstrated in fetal blood samples and in chorionic villus samples, thus permitting antenatal diagnosis during the first trimester (Ward et al, 1983;Rodeck et al, 1983). Although this enzyme polymorphism will be invaluable for the families reported here, because of the low frequency of the 2-allele in the UK will restrict widespread use.…”
Section: Resultsmentioning
confidence: 99%
“…8 Chorionic villus sampling was introduced in the early 80s and since then it has given a new dimension to prenatal diagnosis. 9 Chorionic villus sampling has the great advantage over midtrimester amniocentesis of producing early results. Moreover, rapid analytic techniques have significantly reduced the waiting time between sampling and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its diagnostic potential per se, ultrasound enhances the safety and effectiveness of other diagnostic methods such as amniocentesis, chorionic villus sampling, fetoscopy, and fetal blood sampling (15)(16)(17).…”
Section: Validated Techniques For Biological Markers Ultrasonographymentioning
confidence: 99%
“…Presumably, all diseases and toxic conditions will be defined in molecular terms and diagnosable from a few microliters of blood. This scenario may be upon us before we have the time to grasp the implications of this new technology (17).…”
Section: Molecular Probesmentioning
confidence: 99%